2017
DOI: 10.2174/1874210601711010565
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music Intervention on Dental Anxiety During Dental Extraction Procedure

Abstract: Background:In order to minimize the possibility of unsuccessful dental extraction procedure due to dental anxiety, there are several approaches that can be used, including music intervention.Objective:The objective of this research was to investigate the effectiveness of classical and religious Islamic music on reducing dental anxiety.Materials and methods:Two hundred and twenty-five muslim participants (105 males, 120 females) were recruited for this study and randomly assigned to three groups: classical musi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
0
23
0
4
Order By: Relevance
“…However, in the accordance to another study, participants who listened to classical music tend to show an increase in the NAP level, the systolic blood pressure, as well as the diastolic blood pressure. [38]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the accordance to another study, participants who listened to classical music tend to show an increase in the NAP level, the systolic blood pressure, as well as the diastolic blood pressure. [38]…”
Section: Discussionmentioning
confidence: 99%
“…showed that unlike the participants of the classical music group, the participants who listened to religious Islamic music showed a decrease in systolic blood pressure, diastolic blood pressure, as well as NAP level. [38] Another study by Bradshaw et al . on the effect of religious music on anxiety experienced by the elderly showed that religious music was proven to be effective in reducing anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two in three patients undergoing dental implant surgeries experience moderate or high preoperative DA . Accumulating evidence has revealed that DA is associated with pain perception and patient satisfaction related to dental procedures . Different surgical procedures may cause anxiety for different reasons .…”
Section: Introductionmentioning
confidence: 99%
“…2 Accumulating evidence has revealed that DA is associated with pain perception and patient satisfaction related to dental procedures. [3][4][5][6] Different surgical procedures may cause anxiety for different reasons. 2 Patients may not be able to cooperate with dentists when they experience anxiety during dental treatment, which may increase the amount of time needed and the level of difficulty in performing procedures, thereby causing unsatisfactory treatment results.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been used to reduce patient anxiety during treatment. (3) One of the new techniques of reducing distress is to distract the patient's senses from the environment using various methods and techniques, including music, sound, and image. (4,5) Distraction is based on the principle that each person has a limited attention capacity although when much of this focus is on another stimulus, it is unlikely that the stimulus is undesirable.…”
Section: Introductionmentioning
confidence: 99%